Electroencephalographic sleep elements and outcome in acute encephalopathic patients: a 4‐year cohort study. (2nd April 2014) - Sutter, R.; Barnes, B.; Leyva, A.; Kaplan, P. W.; Geocadin, R. G.
<x xml:space="preserve">Abstract</x> Background and purpose Acute encephalopathy in hospitalized patients is common and associated with high mortality. Preservation of physiological sleep has been associated with favorable outcomes in acute brain injury. It is hypothesized that electroencephalographic presence of sleep elements is associated with good outcome in encephalopathic adults. Methods This observational study was performed at an academic tertiary medical care center. Clinical data, electroencephalogram (EEG) characteristics and outcome of critically ill patients with acute encephalopathy were assessed. EEGs were interpreted regarding the presence of sleep elements (K‐complexes, vertex sharp‐waves and sleep spindles). Associations between sleep elements and outcome (graded by the Glasgow Outcome Scale, GOS) were analyzed. Results One hundred and forty‐two consecutive patients with a median age of 64.5 years (range 18–98) and mean Glasgow Coma Scale 10.4 (± 3.8) were included. Leading etiologies were infections (47.2%), intracranial hemorrhages (14.1%) and ischaemic strokes (10.6%). All EEGs demonstrated encephalopathy patterns and 38% had ≥1 sleep element (27.5% K‐complexes, 31.7% vertex sharp‐waves and 33.8% sleep spindles). Patients without sleep elements were older (P = 0.010) and septic shock was more common (P = 0.014). Amongst sleep elements, K‐complexes were significantly associated with good outcome, even after adjusting for possible confounders (odds ratio for GOS 5 = 2.79, 95% confidence interval 1.16–6.69) and without significant effect modification across subgroups. Conclusions Whilst EEG sleep elements were detected more frequently in patients with favorable outcome, only K‐complexes were significantly and independently associated with good outcome in intensive care unit patients with acute encephalopathy, findings that need to be confirmed in larger prospective studies.